(untitled) (Journal of International Studies, 2020)
Afghanistan is a country that produces the world’s largest single group of refugee emergencies in the world. The causes of refugee flows in Afghanistan are believed to be due to domestic as well as external factors. Domestic factors like local government and different ideologies and external factors such as foreign dominations, have caused conflicts which later led to the flow of refugees in Afghanistan. However, external factors such as foreign domination, have triggered higher flow of refugees in the country. Due to this complexity, the refugee problems still exist. Thus, an understanding on the causes of refugee flow is crucial because the refugee problems need to be tackled from the roots and subsequently this can minimize the problems. Afghanistan is the focal analysis because it produces the largest single group of refugees in the world. The statistics of refugees from Afghanistan are gathered from various sources but mainly from the United Nations High Commissioner for Refugees (UNHCR). The statistics are presented from the 1970s until 2003. A general background of refugee numbers from Afghanistan is presented.